ANALISIS PERBANDINGAN RASIO RETURN ON ASSETS PADA BANK BJB DAN BANK BUKOPIN - Sofyan Marwansyah (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2016)
The bank's financial statements show the financial condition of banks overall. Based on the report can be calculated a number of financial ratios which is commonly used as the basis of assessment the health of banks and assessment of bank performance. Financial ratios that can be used as the analysis is profitability ratio. methods of data collection are observation, interviews and documentation. The data used is secondary data from the consolidated balance sheet, consolidated statements and reports asset quality of BJB bank and Bukopin Bank. The purpose of the research are  to determine homogeneity of variance and analyze differences in profitability ratio of BJB bank and Bukopin bank period 2010 to 2014 by using ratio analysis ROA, BOPO and NIM and data analysis techniques used homogeneity of variance test and independent samples t-test. The results showed that variance of ROA BJB bank and Bukopin bank have equal variances with calculated F value of 1,274 and P-value of 0,289 and thereis differences mean of the ROA significant with t value of 4,614> 2,306 Keywords : Financial ratio, Profitability ratio, ROA